Cloud computing and security. third International Conference, ICCCS 2017, Nanjing, China, June 16-18, 2017, Revised selected papers /: third International Conference, ICCCS 2017, Nanjing, China, June 16-18, 2017, Revised selected papers. Part I : (2017) - Unknown
No abstract available